Borylated strain rings synthesis via photorearrangements enabled by energy transfer catalysis - Shu-Sheng Chen; Yu Zheng; Zhi-Xi Xing; Huan-Ming Huang (Nature Communications)
Abstract Borylated carbocycles occupy a pivotal position as essential components in synthetic chemistry, drug discovery, and materials science. Herein, we present a photorearrangement that uniquely involves a boron atom enabled by energy transfer catalysis under visible light conditions. The boron functional group could be translocated through energy transfer mechanism and valuable borylated cyclopropane scaffolds could be generated smoothly. Furthermore, we showcase a 1,5-HAT (hydrogen atom transfer)/cyclization reaction, which is also enhanced by energy transfer catalysis excited by visible light. This method enables the synthesis of borylated cyclobutane frameworks. These boron-involved photorearrangement and cyclization reactions represent two techniques for synthesizing highly desirable borylated strained ring structures, which offering avenues for the synthesis of complex organic molecules with medicinal and material science applications.